2019
DOI: 10.1016/j.cis.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides at fluid interfaces of food systems

Abstract: Fabrication of next generation polysaccharides with interfacial properties is driven by the need to create high performance surfactants that operate at extreme environments, as for example in complex food formulations or in the gastrointestinal tract. The present review examines the behaviour of polysaccharides at fluid food interfaces focusing on their performance in the absence of any other intentionally added interfacially active components. Relevant theoretical principles of colloidal stabilisation using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 136 publications
(180 reference statements)
1
48
0
Order By: Relevance
“…Similarly, PBP with lower protein than SMBP exhibits smaller d 4,3 values and uniform particle size distribution at the early stages of ageing although both samples destabilise at the end of the storage period. This is in accordance with the findings in other polysaccharide‐stabilised emulsions where conformation of polysaccharides and adsorption strength at the interface seem to be the main mechanism behind their functionality at the oil‐water interface (Kontogiorgos, ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Similarly, PBP with lower protein than SMBP exhibits smaller d 4,3 values and uniform particle size distribution at the early stages of ageing although both samples destabilise at the end of the storage period. This is in accordance with the findings in other polysaccharide‐stabilised emulsions where conformation of polysaccharides and adsorption strength at the interface seem to be the main mechanism behind their functionality at the oil‐water interface (Kontogiorgos, ).…”
Section: Resultssupporting
confidence: 92%
“…Other studies have also reported that increasing molecular weight enhanced emulsion stability by forming thicker polysaccharide layers, which protected the coated oil droplets and reduced coalescence and aggregation (Liu et al , , Funami et al , , Jung & Wicker, ). However, adsorption strength, interfacial rheology and conformational rearrangements may also influence the behaviour of polysaccharides at the interface (Kontogiorgos, ). Consequently, molecular weight cannot alone account for emulsion stability, as for example, SMBC samples with substantially higher Mw than the rest of samples do not perform particularly well during long‐term storage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations